anonymous
  • anonymous
Explain the steps that are necessary to solve 4x - 2(x + 3) = x + 1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Explain the steps that are necessary to solve 4x - 2(x + 3) = x + 1 Can you explain using complete sentences? i really need your help with this problem thanks. -Z.J
anonymous
  • anonymous
you want to get all x on one side
anonymous
  • anonymous
can you solve it for me ? so i can know how to do it?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
First : Get - 2(x + 3) What is the answer of this ?
petiteme
  • petiteme
4x - 2(x + 3) = x + 1 First, distribute 2 inside the parenthesis so 4x - 2(x) - (2)(3) = x + 1 then perform the operaton 4x - 2x - 6 = x+1 2x-6=x+1 To get x, transpose x to the other side and also -6 so 2x-x = 1+6 x=7
anonymous
  • anonymous
Solve for x: 4 x-2 (x+3) = x+1 Distribute -2 over x+3. -2 (x+3) = -6-2 x: 4 x+-6-2 x = x+1 Group like terms in 4 x-2 x-6. Grouping like terms, 4 x-2 x-6 = (4 x-2 x)-6: (4 x-2 x)-6 = x+1 Combine like terms in 4 x-2 x. 4 x-2 x = 2 x: 2 x-6 = x+1 Factor the polynomial, 2 x-6. Factor 2 from the polynomial 2 x-6: 2 (x-3) = x+1 Move everything to the left hand side. Subtract x+1 from both sides of 2 (x-3) = x+1: 2 (x-3)-x+1 = (x+1)-x+1 Look for two terms that sum to zero. (x+1)-(x+1) = 0: 2 (x-3)-(x+1) = 0 Distribute 2 over x-3. 2 (x-3) = 2 x-6: 2 x-6-(x+1) = 0 Distribute -1 over x+1. -(x+1) = -1-x: 2 x+-1-x-6 = 0 Group like terms in 2 x-x-6-1. Grouping like terms, 2 x-x-6-1 = (2 x-x)+(-6-1): (2 x-x)+(-6-1) = 0 Combine like terms in 2 x-x. 2 x-x = x: x+(-6-1) = 0 Evaluate -6-1. -6-1 = -7: x+-7 = 0 Isolate terms with x to the left hand side. Add 7 to both sides: x+(7-7) = 7 Look for two terms that sum to zero. 7-7 = 0: Answer: | | x = 7
anonymous
  • anonymous
Hopefully I helped.
anonymous
  • anonymous
YES THANK YOU ALL ! :)
petiteme
  • petiteme
you're welcome :) anytime :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.